UTILIZING SOCIAL MEDIA FOR PUBLIC HEALTH ADVOCACY AND AWARENESS IN DIGITAL HEALTH COMMUNICATION - Muhtar, St. Murniati; Amir, Andi Subhan; Arya, Nosakros (MSJ : Majority Science Journal, 2024)
The increasing utilization of social media has revolutionized health communication, providing a rapid platform for the dissemination of information and public health advocacy. This study explores the impact of social media in enhancing public health advocacy and increasing public health awareness. Utilizing a mixed-methods approach that combines qualitative and quantitative content analysis, the research findings indicate that: (1) Visually appealing materials, such as infographics and brief videos, are most effective in capturing attention and fostering user engagement for health advocacy purposes. (2) The study also reveals that key elements contributing to the success of health-related social media campaigns include: (a) the power of engaging storytelling, (b) fostering community engagement, and (c) the strategic application of hashtags for wider reach. (3) Leveraging sentiment analysis, we observed a significant positive correlation between the level of positive engagement on social media and the increase in public health awareness.